ANALISIS NILAI-NILAI PENDIDIKAN ISLAM DALAM FILM SERIAL ANAK UPIN & IPIN SEASON KE 10 - Siti Khodijah; Mustopa Kamal; Yosep Farhan Dafik Sahal (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
This descriptive research method uses a semiotic analysis approach. The results showed (1) the value of religious education presented in the 10th film Upin & Ipin season series about recognition of God as Creator; (2) the value of worship education in the 10th child film Upin & Ipin season is reflected in the form of ta'awun, tarawih prayer, shaum ramadhan, tithe, prayer ‘id, respecting time and maintaining cleanliness; and (3) the moral education value obtained in the 10th film Upin & Ipin season series, which is morals to parents, to teachers, to children, to peers, to fellow living beings, and to sick people